Mathematical beliefs: What topics appear, and how has this changed over time? - Muhtarom, Muhtarom; Nizaruddin, Nizaruddin; Sutrisno, Sutrisno; Murtianto, Yanuar Hery; Baldemor, Milagros (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
This research uses the Systematic Mapping Study (SMS) method to identify knowledge trends in beliefs about the nature of mathematics, learning, and learning mathematics and identify new development opportunities for further research. The Systematic Mapping Study (SMS) method is the initial stage for selecting primary sources in a literature study. The Scopus database was used for SMS, then 171 articles were found ready for further analysis. The results show that mathematical belief has become a current research trend. The keywords are